Does metal allergy have relevance in patients undergoing arthroplasty—an electronic survey of surgeon attitudes - Scheidt, Karl B.; Schultzel, Mark; Itamura, John M. (Annals of Joint; Vol 4 (May 2019): Annals of Joint, 2019)
Background: Metallic implants are an integral part of the practice of orthopaedic surgery. Metal hypersensitivity is reported to be from 10−17% of the general population. No consensus exists on how to screen or what changes in treatment plans should be implemented when reported sensitivities to metals exist. Literature review suggests that preoperative testing may influence surgical practice. This study was designed to gain insight to the experience of orthopaedic surgeons as it relates to metal allergies to metallic orthopaedic implants and to examine the trends in screening and evaluating patients who have sensitivities to metals to determine how this data influences treatment. Methods: An online survey of orthopaedic surgeons’ experiences and opinions on the prevalence, screening protocols, and treatment adjustments made when metal hypersensitivity is suspected was performed. A 35-question survey was distributed via orthopaedic surgery specialty societies, orthopaedic surgery departments, and state orthopaedic societies’ email lists. The survey was performed by a commercially available online survey company, which provided data acquisition and analysis. Results: A total of 230 responses were obtained from May 15, 2015 through December 31, 2015. Respondents were primarily from the United States with a small contribution from Canada and other countries. All regions of the United States and all orthopedic specialties were represented. A quarter of respondents have experience with metal allergy to an implant. Most orthopaedic surgeons (69%) believed that metal allergies occur with orthopedic implants, while 18% did not believe that metal allergies occur. Nickel, cobalt, and chromium allergies were most commonly seen. Consultation with an allergist/dermatologist was primarily used for diagnosis. Revision was listed as the first choice of treatment in 47% of respondents, while observation was listed as first choice by 33%. Most surgeons (59%) did not ask patients about metal allergy history. Only a quarter of patient questionnaires inquired about metal allergy. The majority (59%) altered their implant choice with a mild reaction to testing, whereas 29% did not. With a moderate reaction, 72% altered their implant. When the reaction was severe, 64% altered their implant, 12% obtained a second opinion, and 6% did not alter their implant. Conclusions: Orthopaedic surgeons vary in their level of confidence on whether metal allergy to orthopaedic implants exist. Most surgeons believe in metal allergy, but a sizable number do not believe. The prevalence of reported metal allergy to an implant was low. Surgeons tend to alter their choice of implant more frequently as the reaction becomes more severe. Observation and revision surgery are frequently used to treat an allergic reaction. Allergy/dermatology consults are used to diagnose metal allergy, yet a minority of orthopaedic surgeons inquire about metal hypersensitivity in their patients. Greater awareness of a history of hypersensitivity may prevent patient exposure to implants containing metals that they may react to. More evidence is needed to establish a connection between metal sensitivity and the occurrence of pain and implant loosening following arthroplasty procedures.